Recombination, cryptic clades and neutral molecular divergence of the microcystin synthetase (mcy) genes of toxic cyanobacterium Microcystis aeruginosa - Tanabe, Yuuhiko (BioMed Central, 2009)
BACKGROUND: The water-bloom-forming cyanobacterium Microcystis aeruginosa is a known producer of various kinds of toxic and bioactive chemicals. Of these, hepatotoxic cyclic heptapeptides microcystins have been studied most intensively due to increasing concerns for human health risks and environmental damage. More than 70 variants of microcystins are known, and a single microcystin synthetase (mcy) gene cluster consisting of 10 genes (mcyA to mcyJ) has been identified to be responsible for the production of all known variants of microcystins. Our previous multilocus sequence typing (MLST) analysis of the seven housekeeping genes indicated that microcystin-producing strains of M. aeruginosa are classified into two phylogenetic groups. RESULTS: To investigate whether the mcy genes are genetically structured similarly as in MLST analysis of the housekeeping genes and to identify the evolutionary forces responsible for the genetic divergence of these genes, we used 118 mcy-positive isolates to perform phylogenetic and population genetic analyses of mcy genes based on three mcy loci within the mcy gene cluster (mcyD, mcyG, and mcyJ), none of which is involved in the production of different microcystin variants. Both individual phylogenetic analysis and multilocus genealogical analysis of the mcy genes divided our isolates into two clades, consistent with the MLST phylogeny based on seven housekeeping loci. No shared characteristics within each clade are known, and microcystin analyses did not identify any compositional trend specific to each clade. Statistical analyses for recombination indicated that recombination among the mcy genes is much more frequent within clades than between, suggesting that recombination has been an important force maintaining the cryptic divergence of mcy genes. On the other hand, a series of statistical tests provided no strong evidence for selection to explain the deep divergence of the mcy genes. Furthermore, analysis of molecular variance (AMOVA) indicated a low level of geographic structuring in the genetic diversity of mcy. CONCLUSION: Our phylogenetic analyses suggest that the mcy genes of M. aeruginosa are subdivided into two cryptic clades, consistent with the phylogeny determined by MLST. Population genetic analyses suggest that these two clades have primarily been maintained as a result of homology-dependent recombination and neutral genetic drift.